Una famiglia, una signoria, una città politica e società nella contea orsiniana di Nola (XIV-XV secolo) - Tufano, Luigi (Regna. Texts and Studies on Institutions, Culture and Memory in Medieval Southern Italy, 2023)
The feudal lordship of Southern Italy and in Southern Italy is a long-lasting historiographic theme, which has taken on new life in recent years. The rethinking of the interpretative categories of the medieval lordship, a series of in-depth analyses of the late-medieval rural societies and the characteristics of the feudal powers, the detailed reconstructions of their forms of administration and management, the investigations into the semantics of representations have allowed the overcoming of that historiographic paradigm of a Southern baronial class which was internally homogeneous and monolithic in its orientations. Aiming to follow this path, this book puts a case study forth: the lordship of the Orsini, counts of Nola, between Terra di Lavoro and Principato Ultra (1293-1528). Using a wide variety of sources (documentary, literary, iconographic and architectural), the author reconstructs how the Orsini were able to entrench themselves within this territory, exposing their network of relationships with Nola's most prominent families, and analysing the processes of their self-representation through artistic patronage.